الأسرة الحسينية 1705م/1881م (دراسة إقتصادية وثقافية) - منال بلواعر (My University, 2025)
Summary: The study revolves around" the Husseinia family 1705-1881AD(an economic and cultural study)", In politics, during the period 1705-1881AD, Tunisia experienced the reign of the Beys of the Husseini dynasty, established on the ruins of the Muradiya dynasty, and the Husseini dynasty went through stages if internal conflicts during this long period.Shealso witnessed the reign of the Beys who marked multiple achievements. Economically, the study included the compoments of the Tunisian economy during the Husseinte period, including agriculture, industry, and commerce, which gave the regency a strong and distinctive economic character. Culturally, that Tunisia witnessed significant progress in the cultural spheres during this period. Numerous cultural institutions were established in Tunisia, including mosques and schools. ---------------------------- الملخص تتمحور هذه الدراسة حول "الأسرة الحسينية 1705م – 1881م (دراسة إقتصادية وثقافية)" فسياسيا شهدت تونس خلال 1705م-1881م حكم بايات الأسرة الحسينية التي قامت على أنقاض الأسرة المرادية، وقد مرت الأسرة الحسينية خلال هذه الفترة بمحطات من الصراعات الداخلية، كما شهدت حكم بايات تركوا بصماتهم من إنجازات متعددة. أما إقتصاديا فشملت الدراسة مكونات الإقتصاد التونسي خلال العهد الحسيني على غرار الجانب الفلاحي والصناعي والتجاري مما أضفى على الإيالة طابعا إقتصاديا تميز بالقوة. أما ثقافيا فقد شهدت تونس تطورا ملحوظا في المجال الثقافي خلال هذه الفترة. تتم تأسيس العديد من المؤسسات الثقافية بما في ذلك الجوامع والمدارس. ------------------------------ Résumé: Cette étude porte sur "La Dynastie Husseinite( une étude économique et culturelle) entre 1705 et 1881" La dynastie husseinite en Tunisie s’est distinguée par son aspect économique à travers des indicateurs multiples durant cette période. Sur le plan économique, l’ère husseinite se caractérise par le développement de l’agriculture du commerce, de l’industrie et de la finance. Sur le plan culturel, la période a vu la fondation de nombreuses institutions, culturelles et écoles. Cela a permis à la culture tunisienne de se distinguer à cette époque par son rayonnement et sa richesse, ce qui a contribué à façonner une identité culturelle tunisienne propre. Mots clés: dynastie husseinite, économie tunisienne, culture tunisienne.
Keywords: الأسرة الحسينية، الحياة الإقتصادية، الثقافة.